The Evolution of the Russian Approach to Multilateral Relations in the Post-Soviet Area - A. Kovalchuk (Vestnik MGIMO-Universiteta)
The article is an attempt to comprehend the changes in the Russian approach to the post-Soviet space. The analysis, based on the official government documents and speeches of Russian officials, reveals the stages of foreign policy in accordance with the current situation unfolding in the international arena. The Russian policy towards the nearest international environment shows changes in tactics, semantics and its focus on certain spheres of cooperation for the realization of its own interests. At the same time, the goal of foreign policy and the importance of "post-soviet space" remained the same. Although the postsoviet space in not a geographical region, Russian foreign policy refers to it as a whole. Russian leaders looked at the CIS as for it to become the "new confederation", with time, it turned out to be a platform to share common interests. The CIS has become a Forum for the elaboration of improvised automatisms and solutions among the interested countries. The CIS is not only a direction of foreign policy, but also the key element of success in Russia's policy towards international major powers. Over time, Russian foreign policy became more influenced by the external environment than the internal political and economic situation. The post-Soviet space in Russian foreign policy has evolved from the space of problems and threats into the arena of potential cooperation and integration processes.